ASSESSMENT OF KNOWLEDGE AND PRACTICES OF NURSING STUDENTS ABOUT PRECAUTIONS AGAINST COVID-19 INFECTION - Haider Abd AL Ameer Twair AL Hamad; Fadia Hussein. Ali (Web of Journals Publishing, 2024)
Nurses must be adequately informed about COVID-19 as well as appropriate practices related to the outbreak, as they will be providing healthcare on the front lines and playing a key role in developing public health practices.
Keywords: knowledge, practices, nursing students, COVID-19 infection